Manual Collection and Semen Characterization in a West Indian Manatee (Trichechus manatus) - Cowart, Jonathan R.; Collins, Danielle M.; Mignucci-Giannoni, Antonio A.; Alejandro-Zayas, Tamara; Rivera-Guzman, Antonio L.; Larkin, Iskande V. (Frontiers in Veterinary Science, 2020)
Limited information is available regarding male reproductive physiology in West Indian manatees (Trichechus manatus). Currently, only basic ultrastructural and morphometric descriptions of the spermatozoon exists; however, there are no reports evaluating any seminal characteristics in this species. Therefore, the aim of the study was to fill current gaps in knowledge regarding semen parameters in West Indian manatees by collecting and characterizing multiple ejaculate samples from a single, adult West Indian manatee. Samples were analyzed for the following semen parameters: volume, agglutination, pH, osmolality, viscosity, concentration, total sperm number, motility and kinematic parameters, morphology, plasma membrane integrity, acrosome integrity, chromatin maturation, and chromatin condensation. All macroscopic semen parameters varied to some extent between samples. Total and progressive motility was high for ejaculates 2 to 5, exceeding 97% and 89%, respectively; however, these parameters decreased dramatically throughout ejaculates 6 and 7. Across all samples, curvilinear velocity, straight-line velocity, and average pathway velocity represented the largest significant differences (p < 0.001) between each of the progression velocity subgroups (rapid, medium, slow). Sperm characteristics, including acrosome integrity (79.8%), chromatin condensation (93.1%), and chromatin maturation (99.5%) were very high; however, high numbers of morphologically abnormal sperm were present (52.9%) and plasma membrane integrity was low (45.1%). These results are the first of their kind for this species and suggest high semen quality, based on multiple ejaculates, in this male West Indian manatee.